1993
DOI: 10.2466/pms.1993.76.3.943
|View full text |Cite
|
Sign up to set email alerts
|

Talkative Children: Verbal Fluency as a Marker for Problematic Peer Relationships in Clinic-Referred Children with Attention Deficits

Abstract: The relationships between attention deficits, hyperactivity, neurodevelopmental performance, and problematic peer relationships were examined in 99 consecutive children (ages 9 to 11 years) referred for school problems to a clinic. Using a teachers' rating scale, 32 children with cognitive inattention and a comparison group of 67 children without cognitive inattention were identified. The former group comprised children who met criteria for Attention Deficit-Hyperactivity Disorder (ADHD). The latter group comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…By contrast, in a brief 2-week summer program with previously unacquainted peers, high verbal ability among children with ADHD may possibly lead to being perceived as a "know it all" or as someone who talks too much. This idea would be consistent with the findings of Sandler et al (1993), who postulate that higher verbal fluency may lead to poorer peer functioning in children with ADHD because these children talk about the wrong things at the wrong times.…”
Section: Moderation By Adhd Status and Gendersupporting
confidence: 88%
See 1 more Smart Citation
“…By contrast, in a brief 2-week summer program with previously unacquainted peers, high verbal ability among children with ADHD may possibly lead to being perceived as a "know it all" or as someone who talks too much. This idea would be consistent with the findings of Sandler et al (1993), who postulate that higher verbal fluency may lead to poorer peer functioning in children with ADHD because these children talk about the wrong things at the wrong times.…”
Section: Moderation By Adhd Status and Gendersupporting
confidence: 88%
“…A study involving a large, community-based sample found that children with ADHD had elevated language problems, but no association between language impairment and social functioning (Sciberras et al, 2014). Furthermore, another study reported that verbal fluency was associated with greater (not less) teacher-reported peer problems among 32 children with high teacher-rated ADHD symptoms (Sandler et al, 1993). The authors postulate that this may have occurred because verbal fluency leads children with ADHD to excessive talking, which alienates peers.…”
Section: Verbal Ability Of Children With Adhdmentioning
confidence: 99%
“…The verbal fluency test has been widely used in clinical settings, and is one of the few assessment tools that can be administered to individuals of various ages. It has been reported that the verbal fluency test is useful in assessing the cognitive deficits in children with various developmental or genetic disorders, including attention deficit hyperactivity disorders (Koziol & Stout, 1992;Sandler et al, 1993), early onset hydrocephalus (Brookshire et al, 1995;Holler et al, 1995), Turner's syndrome (Temple et al, 1996), and dyslexia (Bunn, 1995;Decker, 1989;Levin, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…For example, children with identified learning disabilities frequently display disruptive and aggressive behaviors, possibly due to deficits in attention control and social information processing (Bryan, Wheeler, Felcan, & Henck, 1976;McConaughy & Ritter, 1986;Sandler et al, 1993). Attention deficits are associated with impulsive social information processing and hostile attributional biases (Dodge & Newman, 1981), high rates of boisterous and intrusive social behaviors (Whalen & Henker, 1985), frequent disruptions and rule violations in play (Landau & Moore, 1991), and elevated levels of negative affect in peer interactions (Whalen & Henker, 1985).…”
Section: Nih Public Accessmentioning
confidence: 99%